Kedaulatan dan Keadilan Allah dalam Kitab Obaja serta Relevansinya bagi Kehidupan Masa Kini - Winata, Jordi (Sekolah Tinggi Teologi Adhi Wacana Surabaya, 2023)
The purpose of this Research is to uncover the theological message contained in the Book of Obadiah, the shortest book in the Old Testament, which highlights the sovereignty and justice of God. This study explores key themes such as the judgment of Edom’s sins, the restoration of God's chosen people, and the concept of the